已知\( y = {x^2} + 4x \),则\( dy \)为( ).
A: \( (2x + 4)dx \)
B: \( 2xdx \)
C: \( ({x^2} + 4)dx \)
D: \( ({x^2} + 4x)dx \)
A: \( (2x + 4)dx \)
B: \( 2xdx \)
C: \( ({x^2} + 4)dx \)
D: \( ({x^2} + 4x)dx \)
举一反三
- 下列方程中,不是全微分方程的为( )。 A: \(\left( {3{x^2} + 6x{y^2}} \right)dx + \left( {6{x^2}y + 4{y^2}} \right)dy = 0\) B: \({e^y}dx + \left( {x \cdot {e^y} - 2y} \right)dy = 0\) C: \(y\left( {x - 2y} \right)dx - {x^2}dy = 0\) D: \(\left( { { x^2} - y} \right)dx - xdy = 0\)
- 函数\(z = {e^ { { x^2} - 2y}}\)的全微分为 A: \(<br/>dz = 2x{e^ { { x^2} - 2y}}dx +2{e^ { { x^2} - 2y}}dy\) B: \(<br/>dz = 2x{e^ { { x^2} - 2y}}dx - 2{e^ { { x^2} - 2y}}dy\) C: \(<br/>dz = 2x{e^ { { x^2} - 2y}}dy+ 2{e^ { { x^2} - 2y}}dx\) D: \(<br/>dz = 2x{e^ { { x^2} - 2y}}dy - 2{e^ { { x^2} - 2y}}dx\)
- 函数 $y=x^2 +2x$的微分为 A: $(2x+2)dx$ B: $xdx$ C: $2xdx$ D: $(x+1)dx$
- 设$f(x)=x^2$,$g(x)=2^x$, 那么 $f \circ f \circ g=$ A: $2^{x^4}$ B: $2^{4x}$ C: $x^{2^{2x}}$ D: $x^{2^{x^2}}$
- 已知\( y = {x^2}{e^{ - x}} \),则\( y'' \)为( ). A: \( 2{e^{ - x}} - 4x{e^{ - x}} - {x^2}{e^{ - x}} \) B: \( 2{e^{ - x}} - 4x{e^{ - x}} + {x^2}{e^{ - x}} \) C: 0 D: \( 2{e^{ - x}} - 4x{e^{ - x}} \)